Cell wall polymer mapping in the coenocytic seaweed Codium vermilara (Bryopsidales, Chlorophyta) - Fernández, Paula Virginia (2010)
Cell walls in the coenocytic green seaweed Codium vermilara (Olivi) Chiaje (Bryopsidales, Chlorophyta) are composed of ∼32% (w/w) β-(1→4)-d-mannans, ∼12% sulfated polysaccharides (SPs), and small amounts of hydroxyproline-rich glycoprotein-like (HRGP-L) compounds of the arabinogalactan proteins (AGPs) and arabinosides (extensins). Similar quantities of mannans and SPs were reported previously in the related seaweed C. fragile (Suringar) Hariot. Overall, both seaweed cell walls comprise ∼40%-44% of their dry weights. Within the SP group, a variety of polysaccharide structures from pyruvylated arabinogalactan sulfate and pyruvylated galactan sulfate to pyranosic arabinan sulfate are present in Codium cell walls. In this paper, the in situ distribution of the main cell-wall polymers in the green seaweed C. vermilara was studied, comparing their arrangements with those observed in cell walls from C. fragile. The utricle cell wall in C. vermilara showed by TEM a sandwich structure of two fibrillar-like layers of similar width delimiting a middle amorphous-like zone. By immuno- and chemical imaging, the in situ distribution of β-(1→4)-d-mannans and HRGP-like epitopes was shown to consist of two distinct cell-wall layers, whereas SPs are distributed in the middle area of the wall. The overall cell-wall polymer arrangement of the SPs, HRGP-like epitopes, and mannans in the utricles of C. vermilara is different from the ubiquitous green algae C. fragile, in spite of both being phylogenetically very close. In addition, a preliminary cell-wall model of the utricle moiety is proposed for both seaweeds, C. fragile and C.